Endangered Egyptian Vultures Make Record Appearance at Badli Pond of Jodhpur in Rajasthan - Gehlot, Hemsingh; Adhikari, Tapan; Suthar, Prakash; Gaurav (Discoveries in Agriculture and Food Sciences, 2024)
Rajasthan hosts seven of the nine vulture species found in India, including the endangered Egyptian vulture, which is experiencing a declining population trend. The primary threats contributing to this decline include trichobezoars, predation by feral dogs, exposure to diclofenac, and collisions with high-tension power lines. The Badli Pond, which has recorded an average population of 1575 Egyptian vultures with a maximum count of 1670 ± 30.95 individuals, along with the Keru dumping yard and Arna Jharna, presents an opportunity to be developed into a vulture-safe zone for conservation efforts.